Effects of silicon on the growth and genetic stability of passion fruit - Costa, Bárbara Nogueira Souza; Dias, Gabrielen de Maria Gomes; Costa, Irton de Jesus Silva; Assis, Franscinely Aparecida de; Silveira, Flávia Aparecida da; Pasqual, Moacir (Acta Scientiarum. Agronomy, 2016)
The objective of this study was to determine the silicon concentration that would provide good growth in passion fruit plants. Passion fruit seeds were sown in polystyrene. After 60 days, when they were approximately 15 cm tall, the plants were transplanted into polyethylene pots containing 1.1 kg Tropstrato® substrate. Treatments consisted of four concentrations (0, 0.28, 0.55, and 0.83 g pot-1) of silicon applied as a silicic acid solution 1%. This solution was applied around the stem of the plants (drenched), with the first application being administered 15 days after transplanting. In total, three applications were made at intervals of 15 days. After the last application, the plants were subjected to chemical analysis to determine the silicon concentration and to X-ray microanalysis and flow cytometry. Phytotechnical analyses were performed during the applications. The use of silicon in concentrations of 0.28 and 0.55 g pot-1 provides better growth of the passion fruit, and the absorption and deposition of the silicon in the passion fruit leaves are proportional to the availability of this element in the plant. The roots of the passion fruit plant are silicon accumulators, and the DNA stability and amount are preserved in the silicon-treated passion fruit plants.